2001
DOI: 10.1128/iai.69.6.3906-3915.2001
|View full text |Cite
|
Sign up to set email alerts
|

Ureaplasma urealyticumModulates Endotoxin-Induced Cytokine Release by Human Monocytes Derived from Preterm and Term Newborns and Adults

Abstract: We previously observed that Ureaplasma urealyticum respiratory tract colonization in infants with a birth weight of <1,250 g was associated with increases in the tracheal aspirate proinflammatory cytokines tumor necrosis factor alpha (TNF-␣) and interleukin-8 (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 74 publications
7
64
0
Order By: Relevance
“…In vitro studies demonstrated that U. diversum was able to induce murine macrophages to produce TNF-α in a dose dependent way (ChelmonskaSoyta et al 1994). Furthermore, U. urealyticum stimulates the release of TNF-α by macrophages and monocytes from human umbilical cord blood (Manimtim et al 2001). Infections with U. diversum in the reproductive tract may, at fi rst, not stimulate recruitment of cells to the site.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies demonstrated that U. diversum was able to induce murine macrophages to produce TNF-α in a dose dependent way (ChelmonskaSoyta et al 1994). Furthermore, U. urealyticum stimulates the release of TNF-α by macrophages and monocytes from human umbilical cord blood (Manimtim et al 2001). Infections with U. diversum in the reproductive tract may, at fi rst, not stimulate recruitment of cells to the site.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been recently demonstrated that M. pneumoniae infection induces reactive oxygen species and DNA damage in human lung cells [Sun et al, 2008]. A number of studies show that Ureaplasma urealyticum induce the production of TNF-α, IL-8, IL-6 [Li et al, 2000a;Manimtim et al, 2001;Peltier et al, 2008], NF-B and nitric oxide [Li et al, 2000b] by human macrophages and monocytes. Infection assays in macrophages performed in combination with LPS showed that U. urealyticum enhances the proinflammatory response to a second infection by blocking expression of counterregulatory cytokines (IL-6 and IL-10), predisposing the preterm infant to prolonged and dysregulated inflammation, lung injury, and impaired clearance of secondary infections [Manimtim et al, 2001].…”
Section: Cell Culture Modelsmentioning
confidence: 99%
“…Among premature infants, respiratory tract colonization with genital ureaplasmas has been associated with pneumonia, chronic lung disease, infant wheezing, respiratory distress syndrome, acute respiratory insufficiency, and increased mortality [Cultrera et al, 2006;Kafetzis et al, 2004]. For some infants, ureaplasmal infection triggers a vigorous response in the lungs involving the elevation of adhesion molecules, collagenases, proinflammatory cytokines and neutrophil activation and migration, which increase the risk of developing bronchopulmonary dysplasia characterized by delayed alveolarization, chronic inflammation, and fibrosis [Manimtim et al, 2001;Schelonka & Waites, 2007]. Additionally, free radical generation and oxidative injury induced by recruited neutrophils could contribute to lung damage [Buss et al, 2003].…”
Section: Ureaplasma Urealyticum and Ureaplasma Parvum In Urogenital Amentioning
confidence: 99%
See 2 more Smart Citations